The auditor’s psyche: Unveiling the hidden links between mood, independence, uncertainty, and audit quality in an emerging market - Lam, Tran Khanh (The Economics and Finance Letters, 2025)
This study investigates the complex relationships between auditor mood, auditor independence, environmental uncertainty, and audit quality in a developing economy. Specifically, it examines the direct effects of auditor mood (AUMO) and auditor independence (AUIN) on audit quality (AUQA). Furthermore, the study explores the moderating influence of environmental uncertainty (ENUN), measured by sales volatility, on the relationships between AUMO and AUQA, and AUIN and AUQA. The research hypotheses were tested using panel data derived from Vietnamese listed companies. The sample comprises firm-year observations from 2020 to 2024, resulting in 835 firm-year observations. The Arellano-Bond two-step system generalized method of moments (S-GMM) regression technique was employed for the analysis. The results reveal novel insights specific to the Vietnamese context: (1) AUMO significantly contributes to enhancing AUQA; (2) AUIN was found to have an unexpected negative association with AUQA; (3) ENUN negatively moderates the positive link between AUMO and AUQA, while its moderation of the AUIN-AUQA relationship was found to be positive in the full model; (4) The impact of these psychological and structural factors on AUQA is a multidimensional phenomenon profoundly shaped by contextual factors and intricate interactions among these variables. Our findings provide valuable guidance for policymakers in considering psychological dimensions and context-specific factors when designing regulatory frameworks to foster AUQA in Vietnam. This research illuminates the complex, context-dependent nature of these interactions, providing a nuanced understanding of how specific psychological elements (AUMO), structural attributes (AUIN), and contextual pressures (ENUN) interplay to influence audit outcomes.